ORGANIZATIONAL AND LEGAL MECHANISM OF FINANCIAL INVESTIGATIONS IN LAW ENFORCEMENT ACTIVITY: INFORMATION AND ANALYTICAL APPROACH - VIVCHAR, OKSANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In modern conditions of turbulence of economic processes of activity of law enforcement agencies testifies that effective counteraction to crime is impossible without active use of economic knowledge. Please note that the practical effectiveness of the mechanism for detecting and investigating economic crimes depends to some extent on the study of financial information that characterizes criminal activity. Meanwhile, it should be noted that at the stage of crime detection, financial monitoring of dubious financial transactions is used, inspections and audits of financial and economic activities of economic entities are conducted. At the stage of crime investigation, the timely appointment and conduct of forensic accounting examinations, the involvement of a specialist economist in investigative actions, etc. is important. Combating modern crime involves the integration of legal and economic knowledge, as well as the interaction of operational and investigative units of law enforcement agencies, which are directly involved in detecting and investigating crimes together with experts with economic knowledge.The article examines the conceptual and categorical apparatus of financial investigations and the role of law enforcement agencies in the process of detecting criminal activity. Information and analytical support of financial investigations is substantiated. As a result of scientific research, it is identified according to the classification features of the scheme of legalization (laundering) of criminal means. On the basis of which the three-phase model of legalization (laundering) of proceeds from crime is characterized, which consists of three stages: stages, stratification, integration.
Keywords: financial investigations; law enforcement agencies; law enforcement activities; legalization (laundering) of proceeds from crime; information and analytical activities